Development of newer adsorbents: activated carbons derived from carbonized cassia fistula - Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Salvi, Monal S.; Jain, Saijal; Hadawale, Snehal D.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia fistula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms of the derived adsorbents produced by thermal and chemical activation was examined for two representative cases, desulfurization of transportation fuels and wastewater treatment. The adsorbents were characterized by FTIR, XRD, XPS, and SEM techniques that indicate specific characteristics useful as an adsorbent. A successful application in the real industrial wastewater treatment and comparison with well recognized commercial adsorbents clearly highlights the utility of the developed newer adsorbents in separation science and technology.